Nivel de conocimiento y actitud sobre la hipomineralización molar incisivo (HMI) en cirujanos dentistas del Ministerio de Salud – Maynas ciudad 2025 - Franco Pereira, Astrid Geraldine (2025)
Objective: To assess the level of knowledge and attitude regarding Molar Incisor Hypomineralization (MIH) among dentists working in the Ministry of Health (MINSA) – Maynas city, 2025. Materials and Methods: A quantitative, descriptive, cross-sectional study was conducted with a census sample of 100 dentists from MINSA health centers in Maynas. A validated questionnaire (Aiken’s V = 0.70; KR-20 = 0.73) was used to measure knowledge (diagnosis and treatment dimensions) and professional attitude using a Likert scale. Data were analyzed using SPSS v22, with descriptive statistics and Chi-square tests (p < 0.05). Results: Most dentists (64 %) showed a moderate level of knowledge, 35 % demonstrated a good level, and 1 % a deficient level. Regarding attitude, 46 % showed a very positive and 49 % a positive attitude. No significant association was found between knowledge and attitude (χ² = 4.377; p = 0.357). Conclusion: Dentists from MINSA-Maynas generally display an intermediate level of knowledge but a highly positive attitude toward MIH diagnosis and management.